2014
DOI: 10.1021/ac404175e
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Vapor Generator That Simulates Transient Odor Emissions of Victims Entrapped in the Voids of Collapsed Buildings

Abstract: The design, development, and validation of a dynamic vapor generator are presented. The generator simulates human scent (odor) emissions from trapped victims in the voids of collapsed buildings. The validation of the device was carried out using a reference detector: a quadrupole mass spectrometer equipped with a pulsed sampling (PS-MS) system. A series of experiments were conducted for evaluating the simulator's performance, defining types and weights of different factors, and proposing further optimization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…To analyze closed boundary transmission and its effect on the propagation and signal delay, an experimental setup was created. To generate and to transmit the particles, an odor transmitter was developed [28], [30], [47]- [49]. To detect the sent particles and distinguish them, a membrane inlet mass spectrometer with a quadrupole mass analyzes (QMA) was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze closed boundary transmission and its effect on the propagation and signal delay, an experimental setup was created. To generate and to transmit the particles, an odor transmitter was developed [28], [30], [47]- [49]. To detect the sent particles and distinguish them, a membrane inlet mass spectrometer with a quadrupole mass analyzes (QMA) was used.…”
Section: Methodsmentioning
confidence: 99%
“…A study conducted in [28] showed an experimental transmission of closed-boundary experiment. However, the [47] (1) Carrier gas (Q) introduction into the mixing chamber (2) Mixing chamber (3) Evaporation chamber ( Figure 3) (4) Transmitted chemicals that are released from the chamber. (5) A modulation sequence that is used to create gas pulses [30].…”
Section: Introductionmentioning
confidence: 99%
“…The first part consists of mass flow controllers (MFC) which depending on the message going to be transmitted, closes and releases the valves which control the flow of the N 2 gas. This controlled gas then travels to the evaporation chamber (EC) where the evaporated chemicals in the chamber is carried over to the mixing chamber [34], [36]. For the experiment, volatile organic compounds (VOCs) are used.…”
Section: A Transmittermentioning
confidence: 99%
“…Thus, it is crucial to perform multiple calibration points using the same concentrations, but at various levels of RH%. For gas streams containing mixtures of trace concentrations, the divided dilution flow is superior compared to the direct injection . Here, the water vapor is mixed with the highest flow rate gas stream (dilution gas).…”
Section: Gas Generating Systemmentioning
confidence: 99%